Clean Water Processing through a Filtration System using a Multimedia Filter on River Water in Babak Village, West Lombok Regency - Elsonpurnama Dhea Wunda; Tina Melinda; Hijriati Sholehah (Jurnal Pijar MIPA, 2025)
The quality of river water is influenced by natural factors and human factors. For humans, the river becomes a place to carry out various activities. The type of research used is an experiment and the object of the research is the water of the Babak River, West Lombok Regency which is processed using a filtration method with a simple filtration system from PVC pipes designed with a filter media arrangement, namely zeolite with a thickness of 5 cm, silica sand with a thickness of 15 cm, activated carbon with a thickness of 10 cm, filter foam with a thickness of 5 cm. This study aims to determine the effects of river water quality testing before and after filtration, as well as the effectiveness of the filter media in reducing pollutant levels. The parameters tested are pH, TSS, TDS, COD, BOD, DO, and Total Coliform. Testing was carried out at the Environmental Laboratory of the Mataram Environmental Engineering College. The test results showed that the water from the Babak River did not meet the standards for clean water. The laboratory tests revealed that the water content value exceeded the quality standards for Class III, as specified in Government Regulation No. 22 of 2021, particularly for the BOD and DO parameters. Therefore, further testing was necessary. According to the filtering results, the effectiveness value of the filter media in the upstream part of the river was 35%, in the middle part was 40%, and in the downstream part was 33% for the BOD parameter. For the DO parameter, the effectiveness values of the filter media in the upstream, middle, and downstream parts of the river were 43%, 58%, and 64%, respectively. Filtration can be a medium to reduce BOD and DO levels, making it a renewable alternative that can be used for other water sources.